Efficiency evaluation of BRICS's national innovation systems based on bias-corrected network data envelopment analysis - Ibrahim Alnafrah (Journal of Innovation and Entrepreneurship, 2021)
The very limited studies that tried to measure the efficiency of national innovation systems (NISs) in BRICS economies were limited to the assumption that the innovation process at national level consists of one stage only and got different and conflicting results. Therefore, this study endeavours to measure the efficiency of sub-processes within the BRICS's NISs and identify where the system failure lies in each NIS. Bias-corrected network data envelopment analysis (DEA) is used to measure the efficiency of total NIS and the efficiency of the other sub-processes within the system: (1) knowledge production process (KPP), and (2) knowledge commercialization process (KCP). The results showed that NISs in BRICS economies suffer from low performance in commercializing their outputs of universities and research organizations. While, on the other hand, their performance in creating scientific and technical knowledge is good in comparison to other studied countries. We suggest that the reason behind this imbalance is the network system failure associated with weak institutions and high uncertainty in the economy. In this study, we argue that the problem in BRICS NISs is not a problem of resources, but it is a problem of system management and institutions. Some bridging policies are suggested to be adopted by BRICS economies to improve their innovation performance and overcome the system failure of weak links between universities and industry.
Keywords: 650; BRICS economies; Data Envelopment Analysis; DEA network; Knowledge commercialization; National innovation system; System failures